1992
DOI: 10.1038/bjc.1992.394
|View full text |Cite
|
Sign up to set email alerts
|

Value of epidermal growth factor receptor status compared with growth fraction and other factors for prognosis in early breast cancer

Abstract: Summary The epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein whose expression is important in the regulation of breast cancer cell growth. The relationship between EGFR status (determined by an immunocytochemical assay) and various prognostic factors was investigated in 164 primary breast cancers. Overall 56% of tumours were EGFR-positive and the expression of EGFR was unrelated to axillary node status, tumour size and histological grade; and it was poorly associated with the tumour prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 34 publications
2
20
2
Order By: Relevance
“…HR associated with Ki-67 positivity in this case) from studies with inherent dissimilarities. The observed disparity among the conclusions of different studies, responsible for the observed heterogeneity, can be quantified by applying Bukholm et al (2003) 147 No Ceccarelli et al (2000) 217 Yes Galiegue et al (2004) 117 No Gasparini et al (1992) 164 Yes Haerslev et al (1996) 487 Yes Jalava et al (2000) 414 No Kroger et al (2006) 157 No Kronblad et al (2006) 377 Yes Lampe et al (1998) 142 Yes Liu et al (2000) 225 Yes Michels et al (2003) 104 No Molino et al (1997) 322 Yes Rudas et al (1994) 184 No Tsutsui et al (2005) 249 Yes Yang et al (2003) 147 No…”
Section: Discussionmentioning
confidence: 99%
“…HR associated with Ki-67 positivity in this case) from studies with inherent dissimilarities. The observed disparity among the conclusions of different studies, responsible for the observed heterogeneity, can be quantified by applying Bukholm et al (2003) 147 No Ceccarelli et al (2000) 217 Yes Galiegue et al (2004) 117 No Gasparini et al (1992) 164 Yes Haerslev et al (1996) 487 Yes Jalava et al (2000) 414 No Kroger et al (2006) 157 No Kronblad et al (2006) 377 Yes Lampe et al (1998) 142 Yes Liu et al (2000) 225 Yes Michels et al (2003) 104 No Molino et al (1997) 322 Yes Rudas et al (1994) 184 No Tsutsui et al (2005) 249 Yes Yang et al (2003) 147 No…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes are ampli®ed and/or overexpressed in human mammary tumors. These include growth factor like molecules (int2: Schuuring et al, 1992;Zhou et al, 1988), growth factor receptors (EGFR: Gasparini et al, 1992;Sainsbury et al, 1988, c-ErbB2: Slamon et al, 1987, 1989, other tyrosine kinases (Jacobs and Rubsamen, 1983;Ottenho -Kal et al, 1992;, signaling molecules (GRB7 Stein et al, 1994), transcription factors (c-myc: Berns et al, 1992) and cell cycle regulators (cyclin D1/PRAD-1: Bartkova et al, 1994;Buckley et al, 1993, CDC25B: Galaktionov, 1995. While several genes are ampli®ed in each amplicon (or at each locus), three candidates may be relevant to human disease (erbB-2, c-myc and cyclin D respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Saez et al, 1983). The receptor for epidermal growth factor is a membrane protein (Mr 180 kDa), which has been reported to be a sign of bad prognosis, again in multiple studies (Sainsbury et al, 1987;Gasparini et al, 1992). The proteolytic enzyme, cathepsin D (Mr 52 kDa), has been suggested to be involved in metastasis formation and reported in several studies also to be a sign of bad prognosis when present in high levels (for a review see Rochefort, 1990).…”
mentioning
confidence: 99%